Tailored Polarizing Hybrid Solids with Nitroxide Radicals Localized in Mesostructured Silica Walls. Issue 6 (29th May 2017) - Silverio, Daniel L.; van Kalkeren, Henri A.; Ong, Ta‐Chung; Baudin, Mathieu; Yulikov, Maxim; Veyre, Laurent; Berruyer, Pierrick; Chaudhari, Sachin; Gajan, David; Baudouin, David; Cavaillès, Matthieu; Vuichoud, Basile; et al.
Abstract : Hyperpolarization by dynamic nuclear polarization relies on the microwave irradiation of paramagnetic radicals dispersed in molecular glasses to enhance the nuclear magnetic resonance (NMR) signals of target molecules. However, magnetic or chemical interactions between the radicals and the target molecules can lead to attenuation of the NMR signal through paramagnetic quenching and/or radical decomposition. Here we describe polarizing materials incorporating nitroxide radicals within the walls of the solids to minimize interactions between the radicals and the solute. These materials can hyperpolarize pure pyruvic acid, a particularly important substrate of clinical interest, while nitroxide radicals cannot be used, even when incorporated in the pores of silica, because of reactions between pyruvic acid and the radicals. The properties of these materials can be engineered by tuning the composition of the wall by introducing organic functionalities. Abstract :